The Significance of Tackling Stunting for The Economic Prosperity of A Nation – A Narrative Review - Sitorus, Nova Lidia (Ridwan Institute, 2024)
Stunting is a condition where a child’s length or height is shorter for their age due to chronic malnutrition and recurrent infections that occur in the first 1000 days of life. Based on data from the Ministry of Health, the stunting rate in Indonesia in 2023 was recorded at 21.5 percent, only down 0.1 percent from the previous year which was 21.6 percent. The high prevalence of stunting has serious implications for the nation's economic welfare. This research aims to examine stunting prevention in terms of the economic welfare of a nation. This research uses a narrative review method. The phenomenon of stunting carries profound implications for a nation’s health and economic well-being. Children who experience stunting are predisposed to a higher risk of chronic illnesses, exhibit lower intelligence quotients, and are likely to be less productive in their adult years. These factors can impede the trajectory of a nation’s economic advancement and amplify the strain on its public health infrastructure. From an economic perspective, this manifests as a reduction in income per capita, an escalation in healthcare costs, and a deceleration in economic growth. This underscores the urgent need to address stunting in order to safeguard the future prosperity of the nation.